2011
DOI: 10.3324/haematol.2011.045179
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of red blood cell metabolome in overhydrated hereditary stomatocytosis

Abstract: ABSTRACTmetabolites from purified human RBCs. 8 Here we use this strategy to distinguish metabolic changes in RBCs from OHSt patients in order to fully characterize the metabolic bases of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 18 publications
5
30
0
Order By: Relevance
“…Oxidative damage to erythrocytes has been widely studied to explain destructive events in numerous hematological disorders [37,38]. In the present study, we observed a significant decrease in glucose metabolism enzyme activity of rat RBCs after 6 weeks storage.…”
Section: Discussionsupporting
confidence: 66%
“…Oxidative damage to erythrocytes has been widely studied to explain destructive events in numerous hematological disorders [37,38]. In the present study, we observed a significant decrease in glucose metabolism enzyme activity of rat RBCs after 6 weeks storage.…”
Section: Discussionsupporting
confidence: 66%
“…Oxidative injury to erythrocytes has been widely studied and found to contribute to the destructive events observed in many hematological disorders [45][46][47][48]. In the present study, we observed a significant decrease in glucose metabolism enzyme activity of rat RBCs after exhaustive exercise.…”
Section: Discussionsupporting
confidence: 68%
“…The mutated variants might titrate or liberate a component of the complex associated to the membrane or to the cytoskeleton which could then play a secondary role on the activation of cation transport pathways responsible for the stomatocytosis cation leak. Metabolomics studies were recently performed on red cells of 4 patients expressing the HsRhAG F65S variant [39]. A raise in the concentrations of glycolysis end-products, such as pyruvate or lactate, were found as a metabolic signature of OHSt patients' erythrocytes.…”
Section: Discussionmentioning
confidence: 99%